Assessing the potential of Eddy detection in MIZ using SAR and Lagrangian modeling: A test case on Fram Strait - Sandalyuk, Nikita V.; Khachatrian, Eduard; Budyansky, Maxim (Journal of Sea Research, 2024)
The analysis of ocean eddies in the marginal ice zone via remote sensing and modeling data is a challenging task. However, it is of crucial importance for various scientific applications and anthropogenic activities in the Arctic. Models often struggle to accurately represent eddies near the MIZ due to the intricate nature of sea ice-ocean interactions, unresolved small-scale processes, and coarse resolution. Nevertheless, combining the information provided from both SAR and model data offers promising results that can potentially improve eddy detection accuracy near the MIZ. Furthermore, accurate characterization of the spatial and temporal variability of eddies near the MIZ demands a holistic approach that incorporates multi-platform observations, including numerical models and remote sensing data. This study demonstrates a specific test case on the intercomparison of the eddy signatures located in the MIZ in the Fram Strait based on remote sensing SAR scenes and Lagrangian modeling data from the two global oceanographic reanalysis GOFS 3.1 and GLORYS 12 V1. The study specifically displays the strong agreement in the eddy polarity and synchronism with reality, as well as differences in spatial scales and location of eddy centers. Overall, the obtained results support the further use of the presented approach for studying the eddies in the MIZ regions in the Arctic.